Reading Aristotle : argument and exposition - Wians, William Robert.; Polansky, Ronald M., 1948- (Philosophia Antiqua, 2017)
Reading Aristotle: Argument and Exposition argues that Aristotle's treatises must be approached as progressive unfoldings of a unified position that may extend over a single book, an entire treatise, or across several works. Contributors demonstrate that Aristotle relies on both explanatory and expository principles. Explanatory principles include familiar doctrines such as the four causes, actuality's priority over potentiality and nature's doing nothing in vain. Expository principles are at least as important. They pertain to proper sequence, pedagogical method, the role of reputable views and the opinions of predecessors, the equivocity of key explanatory terms, and the need to scrupulously observe distinctions between the different sciences. A sensitivity to expository principles is crucial to understanding both particular arguments and entire treatises.